TESTPERFORMANCE OF MINIATUR BOILER FOR DRYING KERUPUK WITH VARIOUS PRESSURE AND VARIOUS DIRECTION OF AIR CIRCUITS - Ahmad Maulana Kartika; Aa Setiawan; Wardika Wardika (Universitas Muhammadiyah Metro, 2017)
In the industrial center of kerupuk in Indramayu, drying kerupuk by using boiler is done if the weather conditions are cloudy or rainy. The kerupuk drying process uses the boiler by utilizing a steam pressure of 4 bar and passing it to the heat exchanger (hx) for heating air in the drying chamber. To achieve 4 bar pressure on the boiler takes a long time, about 3-4 hours duration so it is less effective in its use. If the steam working pressure on the boiler is reduced to 3 or 2 bar, it will likely save the drying time of the kerupuk. For that we need to test the process of drying kerupuk with pressure variations 2, 3 and 4 bars in order to know the difference in performance. In addition to variations of vapor pressure, the test is also carried out with variations in the direction of air flow to the position of the dried kerupuk, ie the position of vertikal direction and horizontal direction position but with the same pressure that is 4 bar. The test was carried out on a miniatur kerupuk dryer boiler with a design tailored to the conditions in the field. From the test results obtained the value of loss of drying (LOD) kerupuk at 4 bar pressure has a value of 46.4% and 43.8%, while at pressure 3 and 2 bar LOD values 38.4% and 31.1%. It can be said that the working pressure of 4 bar is indeed an effective pressure to be used in the process of drying the kerupuk. For the combustion efficiency of the boiler also, the pressure of 4 bar is higher when compared to the efficiency at 3 and 2 bar pressure. As for the direction of air flow, the direction of the vertikal position of the kerupuk more effectively used in the process of drying kerupuk compared the horizontal direction.Keywords: boiler, heat exchanger, loss of drying, efficiency.